HUKUM ARISAN DALAM ISLAM - Mokhamad Rohma Rozikin (Nizham Jurnal Studi Keislaman, 2018)
Arisan is a common tradition in Indonesia and also practiced in the countries of Muslims in various parts of the world. Contemporary scholars have different opinions regarding this “muamalah”. Some of them consider it haram and some of them consider it mubah. There are also those who consider it mubah with conditions and there are also those who consider it as makruh. Therefore, it is important to know the strongest opinions among the various fatwas and their arguments. What is the Islamic jurisprudence law related to arisan? From this study, it is expected that those who want to know the ruling of arisan can get good valuable data to position themselves as followers of the haram fatwa of arisan and the mubah fatwa of arisan. This research is a library research with a qualitative approach. After being studied, it was found that the strongest law for arisan is mubah. Arisan is included into mubah due to the fact that arisan is a qordh (debts), while the Islamic law allows the qordh contract and the Messenger of Allah i himself also performed the qordh contract. All the arguments which forbid them can be explained by their weaknesses because they are not in accordance with the facts of arisan and the facts of the dalil which are used as the evidence.